Acute onset collagenous colitis associated with protein‐losing enteropathy. (13th April 2017) - Nakaya, Yuichiro; Kaku Hosokawa, Sawako; Kataoka, Yuki; Hirabayashi, Masataka; Yamamoto, Shuhei; Takasu, Kosho; Kitamura, Satoru; Omae, Takahito; Yoshimatsu, Yuki
Abstract: Collagenous colitis is a cause of chronic diarrhea. We report an atypical case of collagenous colitis, presenting with an acute onset, and associated with protein‐losing enteropathy. An 82‐year‐old woman was admitted with a 1 week history of nausea, appetite loss, and diarrhea. Serum albumin level was low. Protein leakage from the small intestine was found by a Technetium‐99m human serum albumin scintigraphy. We diagnosed the patient with collagenous colitis from pathology findings of multiple biopsies taken from the colon. This case implies that collagenous colitis should be considered in acute watery diarrhea, and that it can cause protein‐losing enteropathy.